NYAI DASIMA AND THE PROBLEM OF INTERPRETATION : INTERTEXTUALITY, RECEPTION THEORY, AND NEW HISTORICISM - Umar Junus (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1999)
Due to the prevalent concept of literature being a document, recording an incident, as well as the lack of proper historical documents, people tend to take for granted that the description of a society in a literary work as an authentic description of the society it describes . Sejarah Melayu